Pd-Catalyzed Direct Diarylation of Sodium Hypophosphite Enables the Synthesis of Diarylphosphonates - Jin Yang; Dangwei Qian; Gangwei Wang; Shangdong Yang (Molecules)
A facile and efficient method for synthesizing diarylphosphinates from alcohols and aryl halides, using stable, green, and readily available sodium hypophosphite as a phosphorus source, is disclosed herein for the first time. This method offers high-efficiency and excellent functional group tolerance, providing a straightforward approach to synthesizing a broad range of diarylphosphinates from green starting materials with moderate to excellent yields.